Cardiac Myosarcoma in a Newborn Infant—A Case Report and Literature Review - Vakrilova, Liliya; Marinov, Rumen; Hitrova-Nikolova, Stanislava; Dobrev, Dobri; Denev, Maxim; Lazarov, Stoyan (Frontiers in Cardiovascular Medicine, 2021)
Background: Malignant cardiac neoplasms are extremely rare in neonates. Prenatal diagnosis is often not available. Initial symptoms can mimic non-cardiac diseases. We present a premature newborn, birth-weight 2480g, 34 gestational weeks, which underwent cardiac surgery due to a cardiac tumor. Case summary: This was a 3-rd pregnancy after two spontaneous abortions to a mother with thrombophilia, diabetes, hydramnios, and retroplacental hаematoma. The baby was admitted to NICU with transitory respiratory failure and inborn infection, hence oxygen-supplementation and antibiotics were initiated. On day 11 a deterioration with tachypnea, high oxygen requirements, significantly increasing C-reactive protein values were noted. Chest radiographs were unremarkable. On day 18 a life-threatening condition with clinical symptoms of shock was identified. Echocardiography showed a large tumor formation in the right atrium, reduced blood flow in the right ventricle and pulmonary artery. On day 19 cardiac surgery was performed: a large tumor with a myxomatous appearance that occupied the cavity of the right atrium and infiltrated the annulus of the tricuspid valve was extirpated. The front wall was restored with a patch. Hemodynamics was temporarily stabilized. On the following day, ventricular fibrillation and asystole occurred. Despite life support efforts, the outcome was lethal. The histological result confirmed leiomyosarcoma of the right atrium and right ventricular hypotrophy. Conclusion: Inborn cardiac sarcomas are extremely rare. The prognosis is poor. Due to fast progression in the third trimester, they can be missed by fetal echocardiography in an earlier pregnancy. The postnatal clinical course is aggressive, not specific until invasive infiltration or obstruction by the tumor mass occurred. In our case, the sarcoma mimicked an inborn infection, followed by nosocomial infection and septic shock. Despite low incidence, cardiac tumors should be kept in mind and echocardiography should be conducted if there are unclear symptoms with progressive deterioration during the neonatal period.